PANDANGAN HUKUM ISLAM TERHADAP KEKERASAN DALAM RUMAH TANGGA (KDRT) - Fatholla, Fatholla (IAIN BONE, 2023)
Domestic violence (DV) is a human rights violation that often targets women and children. In the Islamic context, families are expected to be harmonious institutions filled with love and care. However, DV still frequently occurs, even within Muslim communities. This research examines the Islamic legal perspective on DV and its application in the Religious Court of Situbondo. This study employs a qualitative approach using a case study method at the Religious Court of Situbondo. Data were collected through interviews with judges and analysis of DV case documents submitted to the court. The study found that the application of Islamic law in handling DV cases in the Religious Court of Situbondo is based on justice and victim protection, although challenges remain in its implementation. Evidence such as medical reports and witness testimonies play a crucial role in decision-making. Islamic law plays a significant role in addressing DV cases in the Religious Court, but its integration with positive law, such as the Domestic Violence Eradication Act, faces challenges. Further efforts are needed to harmonize both legal systems in protecting DV victims.